Knowledge-based banking: The bankers’ experience on OKS (Online Knowledge Sharing) - Muhamad Ali, Hafizi; Mohammad Yusof, Zawiyah (Canadian Center of Science and Education, 2009)
This paper outlines the results from a web-based survey of first time users of a bankers online knowledge sharing. Palmer´s web metrics were used to investigate the effects of key website characteristics on intention to return, satisfaction and self-efficacy. Partial least squares estimation was used to estimate both the measurement and structural parameters in our structural equation model. Statistical significance of the main relationships provided strong empirical support for author conceptual framework.